Provenance and early cinema - Bernardi, Joanne; Cherchi Usai, Paolo; Williams, Tami, 1970-; Yumibe, Joshua; Blot-Wellens, Camille; Lacasse, Germain; Ingravalle, Grazia; Christie, Ian; Daugaard, Noemi; Stutz, Olivia Kristina (Early Cinema in Review: Proceedings of Domitor Ser., 2021)
Concerned contributors in Provenance and Early Cinema challenge scholars digging through film archives to ask, ""How did these moving images get here for me to see them?This volume, which features the conference proceedings from Domitor, the International Society for the Study of Early Cinema, 2018, questions preservation, attribution, and patterns of reuse in order to explore singular artifacts with long and circuitous lives.